Intestinal ,occlusion by alimentary foreign bodies.: Simple and combined-mechanism obstruction - Armand Ugon, Alfredo; Fronzuti, Agustín; Perdomo, Roberto; Carrera, Carlos (Cirugía del Uruguay, 1976)
Twelve clinical histories of intestinal obstructions by alimentary foreign bodies are analized. In the simple obturation the ingestion is of foreign substances, and is favored by dentary alterations and stomach operations. As for the mixed obturations, they may be due to the ingestion of different kinds of foreign substances, ·but the obturation is conditioned to. the pre-existence of small-intestine stenosis by brida, hernia, eventrations or tumors.